(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Background: Thyroglossal duct cyst a developmental anomaly present as a congenital cervical masses of neck in children. Objectives: To observe its deferent presentation and evaluate among the children. Materials and methods: This observational cross section study conducted among patients of eighteen years of age present with thyroglossal duct cyst between 2007 to 2012 in the department of ENT and Head- Neck surgery, Dhaka Medical College Hospital, Dhaka. All patients were operated by Sistrunk operation under (excision of total cyst and removal median portion hyoid bone) under general anesthesia. All specimens were histo-pathologically confirmed. Results: Among 24 children with thyroglossal cyst, 15 boys and 9 girls with male female ratio 1.67:1, age ranged from 4 years to 18 years (mean 9.46 std ±4.27). Male (mean 7.53±4.01years) child are younger than female (mean 12.67±2.39 years) child. 66.67% male children were below 10 years of age and 88.89% female children were over 10 years of age. According to the presentation site 17(70.83%) cases were juxtra hyoid, 4(16.67%) were suprahyoid and 3 (12.50%) were infrahyoid. 23 (95.83%) were present as midline swelling, only 1(4.17%) was present as left lateral infrahyoid swelling. 4(16.67%) patient were attended as thyroglossal fistulae with history of intervention. 4(16.67%) patient were developed recurrence followed by surgical resection within two years. Conclusion: Thyroglossal duct cyst present as an asymptomatic midline neck mass around the hyoid region in children. Complete resection along with median portion hyoid bone prevents recurrence. J. Paediatr. Surg. Bangladesh 5(2): 45-53, 2014 (July)